2021
DOI: 10.1038/s41419-020-03347-3
|View full text |Cite
|
Sign up to set email alerts
|

DHA/AA alleviates LPS-induced Kupffer cells pyroptosis via GPR120 interaction with NLRP3 to inhibit inflammasome complexes assembly

Abstract: Pyroptosis is a novel type of programmed cell death associated with the pathogenesis of many inflammatory diseases. Docosahexaenoic acid (DHA) and Arachidonic acid (AA) is widely involved in inflammatory pathological processes. However, the effect and mechanism of DHA and AA on pyroptosis in Kupffer cells are poorly understood. The present study demonstrated that DHA and AA ameliorated lipopolysaccharide (LPS)-induced Kupffer cells pyroptosis by reversing the increased expression of NLRP3 inflammasome complex,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 44 publications
0
21
0
Order By: Relevance
“…Hua et al also found that activation of NLRP3 and caspase-1 in neurons can also lead to neuroinflammation [40]. NLRP3 has been found to be significantly elevated in neurons [41] and microglia [42] in the epileptic brain, which is mainly stimulated by intracellular environment and cell membrane receptor signals [43]. Moreover, GPR120 is a membrane receptor that can be internalized into cells to regulate inflammatory factors under disease conditions [44].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hua et al also found that activation of NLRP3 and caspase-1 in neurons can also lead to neuroinflammation [40]. NLRP3 has been found to be significantly elevated in neurons [41] and microglia [42] in the epileptic brain, which is mainly stimulated by intracellular environment and cell membrane receptor signals [43]. Moreover, GPR120 is a membrane receptor that can be internalized into cells to regulate inflammatory factors under disease conditions [44].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, GPR120 is a membrane receptor that can be internalized into cells to regulate inflammatory factors under disease conditions [44]. When inflammation occurs, interaction of GPR120 and NLRP3 evokes internalization of GPR120 from the cell surface into internal cellular compartments, exerting anti-inflammatory effects [41]. However, such anti-inflammation of GPR120 is still not enough to compensate inflammatory damage in epilepsy; therefore, exogenous GPR120 is necessary for seizure alleviation.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, fish oil, a matrix particularly enriched in ω-3 DHA and EPA, has been extensively studied. All data reported the anti-inflammatory properties of EPA and DHA resulting in a downregulation of NLRP3 gene expression and in a decreased secretion of pro-inflammatory cytokines (IL-1β and IL-18) in obesity models [ 102 , 103 ], in DSS-induced colitis in mice [ 104 ], in LPS-induced Kupffer cells [ 105 ], and in both prefrontal cortex and hippocampus of rats [ 106 ]. Nevertheless, numerous studies have explored the anti-inflammatory mechanisms of PUFAs.…”
Section: Food Components As Nlpr3 Modulatorsmentioning
confidence: 99%
“…More recently, Quingyao et al assumed that DHA-mediated NLRP3 inflammasome inhibition was due to the blockade of high glucose-induced TXNIP via the PI3K/Akt pathway in pre-adipocytes [ 103 ]. Other mechanisms through which ω-3 PUFAs reduce metabolic inflammation may include the G protein-coupled receptor 120 (GPR120) and GPR40, which interact with NLRP3 and inhibited the NLRP3 inflammasome complex assembly [ 42 , 105 ].…”
Section: Food Components As Nlpr3 Modulatorsmentioning
confidence: 99%
“…( Liu et al., 2012 ) revealed that dietary fish oil enhanced the integrity of the intestines through inhibiting TLR4 and NOD2 signaling pathways within breastfed developing porcines post-LPS confrontation. Interestingly, n-3 PUFA, mainly EPA, are able to alleviate LPS-induced Kupffer cells pyroptosis via abolishing NLRP3 inflammasome activation, thus inhibiting subsequent release of cytokines ( Fan et al., 2021 ).…”
Section: Physiological Functions Of Fa On Gut Healthmentioning
confidence: 99%